A review on cyclin-dependent kinase 7 (CDK7) Inhibitors as anticancer agents - Sorno, Rubina Haque (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.